Clinical Trial Design for Alcoholic Hepatitis - Szabo, Gyongyi (Seminars in Liver Disease, 2017)
Alcoholic hepatitis (AH) is an acute and clinically distinct manifestation of alcoholic liver disease. While severe AH causes 30% or higher mortality in 3 months, treatment options are limited and ineffective. Recent advances on the understanding of the pathomechanisms of AH have identified numerous potential targets for new therapeutic interventions. Many of those targets are currently under preclinical testing and/or in human clinical trials for nonalcoholic steatohepatitis. Thus, the field of AH should be ready to launch new efforts and targeted clinical trials for this underserved patient population. There are remaining challenges in designing clinical trials in AH that include definition of the severity of disease, common data elements in clinical trial design, and selection of clinically meaningful endpoints. Future efforts and consensus meetings between regulatory agencies, academic and clinical experts, and industry will be instrumental to advance this emerging and greatly needed field of clinical investigations.
Keywords: alcoholic liver disease; endpoints; common data elements